Analisis Pengaruh Rasio Keuangan: Likuiditas, Aktivitas dan Leverage terhadap Penilaian Kinerja Keuangan Studi Empiris: Perusahaan Manufaktur di Bursa Efek Indonesia Periode 2010 – 2012) - Lambok DR Tampubolon (STIE Indonesia Banking School, 2015)
Financial statements are a reflection of how the condition of a company, which is used for decision making by multiple stakeholders. The financial statements presented are not just specific to the company's internal corporate or other interested parties, but also including the wider community understands or does not understand the financial statements. Therefore, this study was conducted with the aim that the outside community can assess the company's financial performance measure using measuring instruments, namely financial ratio Expected for the outside community is not only assess performance by looking directly how high profit results, but judging performance by measuring the ability of the company.This study is an empirical study on Manufacturing Company listed on the Indonesia Stock Exchange (IDX) in the period 2010-2012 Analysis of the data used is the multiple regression technique. The total of samples used in this study were 30 manufacture companies. The results of this study are that significant and influential independent variable on the dependent variable